GRK5 – A Functional Bridge Between Cardiovascular and Neurodegenerative Disorders - Hendrickx, Jhana O.; van Gastel, Jaana; Leysen, Hanne; Santos-Otte, Paula; Premont, Richard T.; Martin, Bronwen; Maudsley, Stuart (Frontiers in Pharmacology, 2018)
Complex aging triggered disorders are multifactorial programs that comprise multiple alterations in interconnected protein networks over a large range of tissues. To coordinate the generation of these pathological events, it is evident that rather than being randomly organized pathophysiologies that possess a strong aging component such as cardiovascular diseases (hypertensions, atherosclerosis and vascular stiffening) and neurodegenerative conditions (dementia, Alzheimers disease, mild cognitive impairment, Parkinsons disease), they represent a modified version of the intricate molecular aging programs already in place. To control such multidimensional functions there are layers of trophic protein control across these networks mediated by keystone proteins. These proteins interact and regulate multiple signaling pathways to engender a whole somatic phenotype, here we posit that the G protein coupled receptor kinase 5 (GRK5) represents one of these key controllers. Considerable data has emerged, suggesting that GRK5 acts as a bridging factor, allowing signaling regulation in pathophysiological settings to control both the cardiovascular and neurophysiological complications of aging.